The Riddles of Harry Potter : Secret Passages and Interpretive Quests - Wolosky, Shira, 1954- (New York Palgrave Macmillan, 2010)
The Riddles of Harry Potter draws readers into the deeper meanings of these phenomenally successful books, arguing that they launch and pursue interpretive quests in an ongoing effort to understand patterns and their attendant meanings, implications, and consequences.
Include Notes and Index
Keywords: Magic in literature -- Potter, Harry (Fictitious character) -- Riddles in literature